Retentivity of RRAM devices based on metal/YBCO interfaces - Schulman, Alejandro Raúl (2011)
The retention time of the resistive state is a key parameter that characterizes the possible utilization of the RRAM devices as a non - volatile memory device. The understanding of the mechanism of the time relaxation process of the information state may be essential to improve their performances. In this study we examine RRAM devices based on metal / YBCO interfaces in order to comprehend the physics beneath the resistive switching phenomenon. Our experimental results show that after producing the switching of the resistance from a low to a high state, or vice versa, the resistance evolves to its previous state in a small but noticeable percentage. We have measured long relaxation effects on the resistance state of devices composed by metal (Au, Pt) / ceramic YBCO interfaces in the temperature range 77 K - 300 K. This time relaxation can be described by a stretched exponential law that is characterized by a power exponent n = 0.5, which is temperature independent, and by a relaxation time τ that increases with increasing the temperature. These characteristics point out to a non-thermally assisted diffusion process that could be associated with oxygen (or vacancy) migration and that produces the growth of a conducting (or insulating) fractal structure. © 2011 Materials Research Society.